Microglia induce the transformation of A1/A2 reactive astrocytes via the CXCR7/PI3K/Akt pathway in chronic post-surgical pain - Ting Li; Tongtong Liu; Xuhui Chen; Li Li; Miaomiao Feng; Yue Zhang; Li Wan; Chuanhan Zhang; Wenlong Yao (Journal of Neuroinflammation, 2020)
Abstract Background Activated astrocytes play important roles in chronic post-surgical pain (CPSP). Recent studies have shown reactive astrocytes are classified into A1 and A2 phenotypes, but their precise roles in CPSP remain unknown. In this study, we investigated the roles of spinal cord A1 and A2 astrocytes and related mechanisms in CPSP. Methods We used a skin/muscle incision and retraction (SMIR) model to establish a rat CPSP model. Microglia, CXCR7, and the phosphoinositide 3-kinase/Akt (PI3K/Akt) signaling pathways were regulated by intrathecal injections of minocycline (a non-specific microglial inhibitor), AMD3100 (a CXCR7 agonist), and LY294002 (a specific PI3K inhibitor), respectively. Mechanical allodynia was detected with von Frey filaments. The changes in microglia, A1 astrocytes, A2 astrocytes, CXCR7, and PI3K/Akt signaling pathways were examined by enzyme-linked immunosorbent assay (ELISA), western blot, and immunofluorescence. Results Microglia were found to be activated, with an increase in interleukin-1 alpha (IL-1α), tumor necrosis factor alpha (TNFα), and complement component 1q (C1q) in the spinal cord at an early stage after SMIR. On day 14 after SMIR, spinal cord astrocytes were also activated; these were mainly of the A1 phenotype and less of the A2 phenotype. Intrathecal injection of minocycline relieved SMIR-induced mechanical allodynia and reverted the ratio of A1/A2 reactive astrocytes. The expression of CXCR7 and PI3K/Akt signaling was decreased after SMIR, while they were increased after treatment with minocycline. Furthermore, intrathecal injection of AMD3100 also relieved SMIR-induced mechanical allodynia, reverted the ratio of A1/A2 reactive astrocytes, and activated the PI3K/Akt signaling pathway, similar to the effects produced by minocycline. However, intrathecal injection of AMD3100 did not increase the analgesic effect of minocycline. Last, LY294002 inhibited the analgesic effect and A1/A2 transformation induced by minocycline and AMD3100 after SMIR. Conclusion Our results indicated that microglia induce the transformation of astrocytes to the A1 phenotype in the spinal cord via downregulation of the CXCR7/PI3K/Akt signaling pathway during CPSP. Reverting A1 reactive astrocytes to A2 may represent a new strategy for preventing CPSP.